2012
DOI: 10.4103/0019-5413.98834
|View full text |Cite
|
Sign up to set email alerts
|

Functional and oncologic outcomes after excision of the total femur in primary bone tumors: Results with a low cost total femur prosthesis

Abstract: Background:The extent of tumor may necessitate resection of the complete femur rarely to achieve adequate oncologic clearance in bone sarcomas. We present our experience with reconstruction in such cases using an indigenously manufactured, low-cost, total femoral prosthesis (TFP). We assessed the complications of the procedure, the oncologic and functional outcomes, and implant survival.Materials and Methods:Eight patients (four males and four females) with a mean age of 32 years, operated between December 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
3
26
2
Order By: Relevance
“…These data are considerably higher compared to infection rates described in the recent literature with a reported range from 0 to 35% in TFR [35, 79, 11]. A possible explanation for these high infection rates is the number of revision surgeries prior to implantation of TFR (56 in 18 patients).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These data are considerably higher compared to infection rates described in the recent literature with a reported range from 0 to 35% in TFR [35, 79, 11]. A possible explanation for these high infection rates is the number of revision surgeries prior to implantation of TFR (56 in 18 patients).…”
Section: Discussionmentioning
confidence: 69%
“…The most common cause for Type I failure was aseptic wound dehiscence ( n  = 11), followed by hip dislocation ( n  = 5) and knee arthrofibrosis ( n  = 2). In the literature, reported rates vary between 0% and 45% [35, 7, 11] for Type I complications. It is known from large series with primary hip arthroplasty that 75% of dislocations occur within the first two months after implantation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Protocols for postoperative immobilization were described in 19 studies. Two studies reported 6 weeks in an abduction brace following total femoral replacement . The immobilization protocol following limb salvage with a proximal femoral megaprosthetic was not described.…”
Section: Resultsmentioning
confidence: 99%
“…Puri et al reported that hip flexion was limited to 60 degrees for 6 weeks following limb salvage with a total femoral megaprosthetic. Range of motion restrictions following limb salvage with a proximal femoral replacement were not described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation